Analysis of Problem-Solving Ability in Solving Open-Ended Problems of Junior High School Students on Social Arithmetics Material - Ahmad, Rahmawati N.; Kobandaha, Putri Ekawaty (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study aims to determine students' problem-solving abilities in solving open-ended problems in social arithmetic. Problem-solving ability refers to students’ capacity to understand problems, plan appropriate strategies, carry out solutions, and evaluate the results. The research method used in this study is descriptive with a qualitative approach. Data collected in this study were taken from problem-solving ability test results and interviews. The study subjects were seventh-grade students of SMP Negeri 1 Botupingge in the 2025/2026 academic year, each of whom was selected using purposive sampling based on their high, medium, and low problem-solving ability levels. The obtained data were then reduced and analyzed qualitatively, taking into account indicators of the problem-solving ability process. The results show that students with high problem-solving abilities demonstrated excellent problem-solving abilities across almost all indicators. Meanwhile, students with moderate problem-solving abilities were at a sufficient level but were not yet stable and still required guidance, especially in planning and interpreting solutions. Meanwhile, students with low problem-solving abilities had not yet mastered problem-solving skills and required intensive learning intervention.